Metals concentrations in transitional and coastal waters by ICPMS and voltammetry analysis of spot samples and passive samplers (DGT). (June 2022) - Caetano, Miguel; Correia dos Santos, Margarida M.; Rosa, Nuno; Carvalho, Inês; Rodríguez, José Germán; Belzunce-Segarra, María Jesús; Menchaca, Iratxe; Larreta, Joana; Sanz, Marta Rodrigo; Millán-Gabet, Vanessa; Gonzalez, Jean-Louis; Amouroux, Isabelle; et al.
Abstract: This study investigates the relationships among Ni, Cd and Pb's different chemical forms determined by different methodologies in coastal and transitional waters across a broad geographical scale. Concentrations were measured in spot samples and through passive sampling (DGT). High variability of metal concentrations was found among sampling sites and methodologies due to natural water fluctuations rather than to a given metal or method. Total dissolved metal concentrations in spot samples were lower than the EQS-WFD values. The labile fractions of Cd and Pb, measured in spot samples by Anodic Stripping Voltammetry and by DGT-ICPMS, were highly correlated. Similar labilities were found for Cd, while for Pb, the ASV labile fraction was ≈50% lower. These results reflect the pool of mobile and labile species available towards each technique kinetic window, and they seem not to be affected by discrete sampling flaws. Highlights: Broad geographical study on priority metals by spot measurements and passive samplers Dissolved metal concentrations were below the EU WFD's guideline levels. Similar Cd-labile concentration by ASV and DGT Different degrees of heterogeneity of Cd and Pb complexes in estuarine waters DGT is more suitable for monitoring marine systems with high variability.